The effects of a parenting program on parental stress and perception of child behavior - Fisher, Robert M., III (Kansas State University, 2014)
Assessment of parenting stress and child acting-out behavior was measured via pretest and posttest over the length of a seven-session parenting program, the Becoming a Love and Logic Parent program (BLLP). All participants (n=86) were randomly placed in either a seven-session BLLP program group (n=56) or placed on a waitlist (n=30) and offered the BLLP program following the completion of the posttest. The BLLP program is a widely used parenting program with limited data available as to the effectiveness of the program. The data that are available utilizes the Becoming a Love and Logic Parent Before and After Questionnaire. A measurement tool designed specifically to measure the BLLP program. This study utilized two measurement tools widely used to evaluate parenting programs, the Parenting Stress Index/Short Form (PSI/SF) and the Eyberg Child Behavior Inventory (ECBI), in hopes of providing data that can be compared to other parenting programs. Levels of parenting stress were measured with a widely used index, the PSI/SF. The PSI/SF provides a Total Stress (TS) score and scores from three scales measuring different aspects of parenting stress: Parental Distress (PD), Parent-Child Dysfunctional Interaction (P-CDI), and Difficult Child (DC). Child acting-out behavior was measured with the ECBI. The ECBI measures disruptive child behavior using two scales: Intensity scale and a Problem scale. The intensity scale provides information regarding the frequency of certain acting-out behaviors, and the problem scale provides information as to whether or not parents view that particular behavior as problematic. All participants were parents or caregivers of elementary school students from a large suburban school district near Kansas City, Missouri. The group was homogenous in nature and had higher income and education levels than the average for the district and state, making it difficult to generalize finding from the study. Due to time and space limitations and attrition, the sample size of the study was small (n=86), which likely contributed to the outcome of the study. The six hypotheses were not supported in this study. Though a decrease in parenting stress occurred for both treatment group and control group participants, there was not a statistically significant difference between the two groups on any of the PSI/SF scales. Child acting-out behavior also decreased for both the treatment group and the control group; however, there was not a statistically significant difference between the two groups. Further study on the effectiveness of the BLLP program is recommended.
Keywords: Parenting stress; Love and Logic; Child acting-out behavior; Parenting education; Behavioral Sciences (0602); Individual & Family Studies (0628); School Counseling (0519)